Psychological and Social Determinants that Influence Interest in Residential Photovoltaic (RPV) - Ayu Nirmala Putria; Metta Nirmala Tjungandib; Nathanael Nirmala Pavitac; Satriya Nirmala Prayogad (Indonesian Business Review, 2019)
This study aims to assess the psychological and social determinants that influence interest towards RPV through an empirical investigation of a new survey-based dataset collected in Jakarta Metro, Indonesia. The theory of planned behaviour (TPB) framework was tested using survey data from 174 non-adopters, providing recommendations of potential intervention for policy makers and RPV installers in alleviating key barriers of RPV adoption. Overall, each of TPB components; attitudes, subjective norms and perceived behavioral control have significant direct and indirect impact towards interest. Individuals perceiving RPV personally and environmentally beneficial are more interested in RPV. Perception of RPV adoption will be supported by peers also increases interest. In contrast, belief of unsuitable house decreases interest. Notably, individuals seeing RPV as a complex technology are more interested to gain information about RPV.